Challenges in Designing and Developing English for Specific Purposes in ELT - Ester Kinasih Silalahi; Bahagia Saragih; Anissa Salsabila; Aisyah Purnama Nasution; Jumita Simbolon (Universitas Islam Negeri Palopo, 2026)
English for Specific Purposes (ESP) is a branch of English language teaching that addresses the specialized linguistic needs of learners with particular professional or academic goals. The development of ESP programs is grounded in a systematic analysis of learners' objectives, needs, and target tasks. In this context, teachers are responsible for designing courses, setting learning objectives, fostering a supportive learning environment, and evaluating student progress, while learners are characterized by their specific motivation, subject-matter knowledge, and individual learning approaches. Nevertheless, ESP instruction presents numerous challenges. Teacher-related challenges include inadequate teaching materials, insufficient professional preparation, and a lack of theoretical grounding. Student-related challenges encompass limited English proficiency, poor vocabulary mastery, and difficulty using ESP terminology effectively. Environmental challenges involve limited instructional resources, overcrowded classes, and excessive examination pressure. This study aims to examine the roles of teachers and students, identify the challenges encountered in ESP instruction, and provide an overview of ESP concepts and teaching strategies within the broader framework of English Language Teaching (ELT).